Eyes wide shut? The US house market bubble through the lense of statistical process control - Michael Berlemann; Julia Freese; Sven Knoth (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2012)
While most economists agree that the recent worldwide financial crises evolved as a consequence of the US house price bubble, the related literature yet failed to deliver a consensus on the question when exactly the bubble started developing. The estimates in the literature range in between 1997 and 2002, while applications of market-based-procedures deliver even later dates. In this paper we employ the methods of statistical process control (SPC) to date the likely beginning of the bubble. The results support the view that the bubble on the US house market already emerged as early as 1996. We also show that SPC in general might be a useful tool in constructing early warning systems for asset price bubbles.
Keywords: C32; E44; 330; statistical process control; real estate; asset prices bubbles; early warning systems